2017
DOI: 10.1620/tjem.242.9
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Possible Etiology of Hospital-Acquired Pneumonia Using a Clone Library Analysis in Japan

Abstract: Obtaining precise etiological information regarding causative bacteria is important for the proper use of antimicrobials in hospital-acquired pneumonia (HAP), which is associated with a high rate of mortality. The aim of this study was to comparatively investigate the bacterial diversity in bronchoalveolar lavage fluid (BALF) in Japanese patients with HAP by the clone library method using the 16S rRNA gene. This study included Japanese patients with HAP who were treated at our hospital and referring hospitals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…are among the commensal flora of the nasopharynx [32], a causative role in pneumonia was recently described [33][34][35][36]. The identification of Corynebacteria subspecies is now possible using new diagnostic technologies, such as matrix-assisted laser desorption ionization time of flight mass spectrometry and 16S rRNA gene sequencing [13,[33][34][35]37]. Based on such studies, Clariot et al suggested that Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…are among the commensal flora of the nasopharynx [32], a causative role in pneumonia was recently described [33][34][35][36]. The identification of Corynebacteria subspecies is now possible using new diagnostic technologies, such as matrix-assisted laser desorption ionization time of flight mass spectrometry and 16S rRNA gene sequencing [13,[33][34][35]37]. Based on such studies, Clariot et al suggested that Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…are among the commensal ora of the nasopharynx [32], a causative role in pneumonia was recently described [33][34][35][36]. The identi cation of Corynebacteria subspecies is now possible using new diagnostic technologies, such as matrix-assisted laser desorption ionization time of ight mass spectrometry and 16S rRNA gene sequencing [13,[33][34][35]37]. Based on such studies, Clariot et al suggested that Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports investigating pneumonia showed that there was a higher ratio of patients with mixed infections of healthcare‐associated pneumonia (HCAP) and hospital‐acquired pneumonia (HAP) compared to patients with community‐acquired pneumonia (CAP). In addition, streptococci were highly detected in elderly pneumonia patients and pneumonia patients with poor general health conditions . In patients with bacterial pleuritis, culture‐based mixed infection was reported in 9.8%–24.0% of patients, with insufficient data detailing the combination of bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, streptococci were highly detected in elderly pneumonia patients and pneumonia patients with poor general health conditions. [14][15][16]26 In patients with bacterial pleuritis, culture-based mixed infection was reported in 9.8%-24.0% 25,27,28 of patients, with insufficient data detailing the combination of bacterial species. In this study, 10 patients were categorized in the 'mixed bacterial-dominant' group and 9 of 10 (90%) patients in the 'mixed bacterial dominant' group were also sorted into the obligate anaerobic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation